Postbreeding elevational movements of western songbirds in Northern California and Southern Oregon. Issue 19 (23rd August 2017) - Wiegardt, Andrew; Wolfe, Jared; Ralph, C. John; Stephens, Jaime L.; Alexander, John
Abstract: Migratory species employ a variety of strategies to meet energetic demands of postbreeding molt. As such, at least a few species of western Neotropical migrants are known to undergo short‐distance upslope movements to locations where adults molt body and flight feathers (altitudinal molt migration). Given inherent difficulties in measuring subtle movements of birds occurring in western mountains, we believe that altitudinal molt migration may be a common yet poorly documented phenomenon. To examine prevalence of altitudinal molt migration, we used 29 years of bird capture data in a series of linear mixed‐effect models for nine commonly captured species that breed in northern California and southern Oregon. Candidate models were formulated a priori to examine whether elevation and distance from the coast can be used to predict abundance of breeding and molting birds. Our results suggest that long‐distance migrants such as Orange‐crowned Warbler ( Oreothlypis celata ) moved higher in elevation and Audubon's Warbler ( Setophaga coronata ) moved farther inland to molt after breeding. Conversely, for resident and short‐distance migrants, we found evidence that birds either remained on the breeding grounds until they finished molting, such as Song Sparrow ( Melospiza melodia ) or made small downslope movements, such as American Robin ( Turdus migratorius ). We conclude that altitudinal molt migration may be a common, variable, and complex behavior among western songbird communities and is related to other aspects of a species' natural history, such as migratory strategy. Abstract : At least a few species of western Neotropical migrants are known to undergo short‐distance upslope movements to locations where adults molt body and flight feathers (altitudinal molt migration). Our results suggest that long‐distance migrants such as Orange‐crowned Warbler (Oreothlypis celata) moved higher in elevation, and Audubon's Warbler (Setophaga coronata) moved farther inland to molt after breeding. Conversely, for resident and short‐distance migrants, we found evidence that birds either remained on the breeding grounds until they finished molting, such as Song Sparrow (Melospiza melodia), or made small downslope movements, such as American Robin (Turdus migratorius).